Bioremoval efficiency and metabolomic profiles of cellular responses of Chlorella pyrenoidosa to phenol and 4-fluorophenol. Issue 1 (10th March 2023) - Li, Min; Ma, Lu; An, Yajing; Wei, Dongbin; Ma, Haijun; Zhu, Juanjuan; Wang, Cuiping
Abstract: We examined the growth tolerance, bioremoval efficacy, and metabolomic profiles of the cellular responses of Chlorella pyrenoidosa to phenol and 4-fluorophenol. We found that C. pyrenoidosa can tolerate exposure to 100 mg/L of phenol and 4-fluorophenol, and the growth of algal cells had a significant hormesis of inhibition first and then promotion. Up to 70% bioremoval of phenol and 4-fluorophenol may occur after 240 h of treatment. Superoxide dismutase (SOD) and catalase (CAT) activities, malondialdehyde (MDA) content, and reactive oxygen species (ROS) in algal cells in the phenol- and 4-fluorophenol-treated groups were similar or lower than in the control group. Furthermore, photosynthetic pigment and glycerophospholipid contents were significantly upregulated in both phenol- and 4-fluorophenol-treated groups, as indicated by the metabolomic analysis of C. pyrenoidosa, resulting in the vigorous growth of algal cells compared to the control group. Therefore, C. pyrenoidosa can be an excellent biosorbent for phenol and 4-fluorophenol. HIGHLIGHTS: Chlorella pyrenoidosa can well tolerate 100 mg/L of phenol or 4-fluorophenol exposure. 100 mg/L phenol or 4-fluorophenol can be bioremoved by >70% after 240 h of treatment. Significant hormesis in algal growth was observed during the treatment. Growth promotion is attributed to chlorophyll and glycerophospholipid accumulation. Graphical Abstract